Expression of VEGFR-3 in intrahepatic cholangiocarcinoma correlates with unfavorable prognosis through lymphangiogenesis - Sha, Meng (Int J Biol Sci, 2018)
Background & aims: VEGFR-3 has been shown of great significance in lymph node metastasis and some malignancies, however, its expression in tumors and impact on outcome of intrahepatic cholangiocarcinoma (iCCA) remains unknown. The aim of this study was to assess the role of VEGFR-3 positive tumors for prognosis of iCCA and tumor-associated lymphangiogenesis. Methods: Clinicopathological features, prognostic factors and survival rate were analyzed to evaluate the influence of VEGFR-3 positive expression on prognosis of iCCA. In addition, tumor-associated lymphangiogenesis quantified as micro-lymphatic vessel density (MLVD) was assessed to explore the correlation between VEGFR-3 expression and lymph node metastasis for iCCA. Results: Patients with VEGFR-3 positive tumors had increased lymph node metastasis (p=0.025) and were more likely to suffer from tumor recurrence compared with VEGFR-3 negative tumors (p<0.001). VEGFR-3 expression in tumors was identified as an independent prognostic factor for both overall and recurrence-free survival in surgical resected patients with iCCA. In addition, higher MLVD was significantly associated with VEGFR-3 positive expression in tumors (p<0.001), which facilitate lymph node metastasis and significantly worse survival rates. Conclusions: Our study reveals that VEGFR-3 positive expression in tumors represents an independent prognostic factor for both overall and recurrence-free survival in hepatic resected patients with iCCA. VEGFR-3 positive tumors favor lymph node metastasis, tumor recurrence and worse outcomes through tumor-associated lymphangiogenesis.